Current advances in multimodal imaging in geographic atrophy secondary to age-related macular degeneration: A review - Amy C. Cohn; Robyn H. Guymer (Taiwan Journal of Ophthalmology)
As we move toward an era in which there will be treatment options for geographic atrophy (GA) secondary to age-related macular degeneration, the need to accurately understand and interpret multimodal imaging (MMI) for the condition is paramount. This review discusses the evolution of MMI in GA and how it has led to a greater understanding of different phenotypes and risk factors for progression. These advancements have allowed novel imaging biomarkers to be used as end points in large interventional studies exploring new therapies for GA treatment. Due to differences in drug approval timing, ophthalmologists in some jurisdictions are already treating patients with complement inhibiting intravitreal therapies and using MMI to guide management. Cementing knowledge of how GA appears on MMI and evolves over time will be vital for best practice as these interventions become more widely available.